2019
DOI: 10.31616/asj.2018.0284
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Cultural Adaptation, Validity, and Reliability Study of the Turkish Version of the Back Pain Functional Scale

Abstract: Study Design Prospective study. Purpose To investigate the cross-cultural adaptation, validity, and reliability of the Turkish version of the Back Pain Functional Scale (BPFS). Overview of Literature Low back pain is a common disorder in the population that negatively affects the patient’s daily, professional, and social life. Self-report questionnaires are important to precisely evaluate back pain and making better and appropriate treatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 27 publications
3
8
0
Order By: Relevance
“…The RMDQ is recommended to be used in combination with other measures when low back pain is associated with psychological or social problems. Compared with RMDQ, the BPFS has better internal consistency, test-retest reliability, and point estimate of susceptibility to change, suggesting its superiority over RMDQ (18,22,29). However, we did not use RMDQ for the assessment of convergent validity assuming a better correlation between BPFS and FRI.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The RMDQ is recommended to be used in combination with other measures when low back pain is associated with psychological or social problems. Compared with RMDQ, the BPFS has better internal consistency, test-retest reliability, and point estimate of susceptibility to change, suggesting its superiority over RMDQ (18,22,29). However, we did not use RMDQ for the assessment of convergent validity assuming a better correlation between BPFS and FRI.…”
Section: Discussionmentioning
confidence: 99%
“…In the Turkish version of the questionnaire Maras et al (18) recruited only patients with chronic low back pain in order to obtain a homogeneous group. Tests by Kaiser Meyer Olkin and Bartlett showed that the sample was suitable and adequate for factorial analysis, which revealed that the BPFS had a single factor structure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This consequence is consistent with results of BPFS in other languages. [6][7][8] Several limitations of the study should be noted. First, although simplified Chinese is the official language of China, China is multi-ethnic, most of which have their own language.…”
Section: Discussionmentioning
confidence: 99%
“…7 The original English BPFS is known for its simplicity, good reliability, and validity and has been translated into Persian 6 and Turkish. 8 China is one of the countries with the largest number of LBP patients. However, so far, there is no Chinese version of BPFS for this population.…”
mentioning
confidence: 99%